Effect of natural and synthetic antioxidants on the oxidative stability of walnut oil under different storage conditions. - Martinez, Marcela Lilian (2013)
The aim of the work was to evaluate the combined effects of the storage condition (six months under fluorescent light e 800 Lux e or darkness condition, both at room temperature) with the addition of natural (rosemary extract, RE) and synthetic (ascorbyl palmitate - AP -, and Tert-butylhidroquinone - TBHQ) antioxidants on quality indices related to walnut oil (WO) oxidative stability. Neither RE nor synthetic antioxidants contributed markedly on inhibiting photo-oxidative degradation, resulting in significantly increased amounts of primary and secondary oxidation products in oils exposed to light. Under darkness-storage condition, the addition of the mentioned antioxidants significantly reduced lipid oxidation and improved oil shelf life. Oils added with RE e alone or in combination with TBHQ or TBHQ plus AP e maintain an acceptable quality at least up to six months of storage. Results from this work stressed the influence of the illumination condition on WO oxidative stability, suggesting that this oil should be stored in containers with light-barrier properties, and may be added with the antioxidants examined in the current study.